Effect of input noise on phase coherence in a lattice of memristors acting as a voltage divider. Issue 3 (17th March 2017) - Frasca, Marco; Farina, Alfonso; Griffiths, Hugh
Abstract : It is known that Fibonacci numbers emerge from a network of voltage dividers comprising just resistors. The authors find that the same happens to a lattice of memristors as recently devised. Between the memristor dividers there is a phase coherence with respect to a sinusoidal input signal. Interestingly, they show that the effect of Gaussian distributed random noise, which adds to the voltage signal at the input of the memristor lattice, may affect the coherence. It is shown that when the signal‐to‐noise ratio goes below 3 dB and the number of dividers in the lattice is ten there is an abrupt reduction of phase coherence typical of non‐linear systems. This behaviour does not happen with a lattice of normal resistors. A tolerance analysis of the classical resistor components as well as of the memristor parameters is also presented.